Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 140156 species occurrences available in GBIF matching the query: { "Country" : [ "is Mongolia" ] } The dataset includes 140156 records from 274 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000299-150512124619364/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences